 Mathematics
19 July, 23:15

# Solve the system of linear equations.6x - 2y = - 182x - 2y = - 2

+3
1. 20 July, 00:54
0
x = - 4

y = - 3

Step-by-step explanation:

to solve the system of linear equation we say that let

6x - 2y = - 18 ... equation 1

2x - 2y = - 2 ... equation 2

from equation 2

2x - 2y = - 2 ... equation 2

2x = - 2 + 2y

divide both sides by 2

2x/2 = (-2 + 2y) / 2

x = (-2 + 2y) / 2 ... equation 3

substitute for x in equation 1

6x - 2y = - 18 ... equation 1

6[ (-2 + 2y) / 2] - 2y = - 18

-6 + 6y - 2y = - 18

collect the like terms

6y - 2y = - 18 + 6

4y = - 12

divide both sides by the coefficient of y which is 4

4y/4 = - 12/4

y = - 3

put y = - 3 in equation 3

x = (-2 + 2y) / 2 ... equation 3

x = - 2 + 2 (-3) / 2

x = - 2-6/2

x = - 8/2

x = - 4

therefore the value of x and y in the equation is - 4 and - 3 respectively.
2. 20 July, 01:02
0
x = - 4, y = - 3.

Step-by-step explanation:

Solving: 6x-2y = - 18 2x-2y = - 2 Using Substitution Method. Expressing x as a function of y (from the first equation) x = (-18 + 2y) / 6 Substituting this expression into the second equation: 2 (-18-2y) / 6-2y = - 2 then Simplifying this expression: (-8) y = 24 or y = - 3 Now you can, substitute y = - 3 back into the x expressed as a function of y: x = (-18+2y) / 6 = - 4